Teaching Race, Colonialism, and Theology in a Joint Project in North America and Africa: Insights from the Project - Holder Rich, Cynthia (Religious education, 2022)
How do race and lived experiences of this construct impact student theological understandings? We embarked on a joint pedagogical venture spanning two continents about race and theology with groups of students whose encounters with race and its impacts on theology were markedly different—including students whose lives and education have been formed by colonialism and its continuing legacies, and students whose grasp of theological systems had hardly addressed the effects of racism on theology. In this article, we share what we learned and offer recommendations for others looking to use this as a model.